Tension and elasticity contribute to fibroblast cell shape in three dimensions - Brand, Christoph A.; Linke, Marco; Schwarz, Ulrich S. (Biophysical journal, 2017)
The shape of animal cells is an important regulator for many essential processes such as cell migration or division. It is strongly determined by the organization of the actin cytoskeleton, which is also the main regulator of cell forces. Quantitative analysis of cell shape helps to reveal the physical processes underlying cell shape and forces, but it is notoriously difficult to conduct it in three dimensions. Here we use direct laser writing to create 3D open scaffolds for adhesion of connective tissue cells through well-defined adhesion platforms. Due to actomyosin contractility in the cell contour, characteristic invaginations lined by actin bundles form between adjacent adhesion sites. Using quantitative image processing and mathematical modeling, we demonstrate that the resulting shapes are determined not only by contractility, but also by elastic stress in the peripheral actin bundles. In this way, cells can generate higher forces than through contractility alone.